Genotype-Phenotype Correlations in Corneal Dystrophies: Advances in Molecular Genetics and Therapeutic Insights - Liskova, Petra; Skalicka, Pavlina; Dudakova, Lubica; Vincent, Andrea L (Clinical & experimental ophthalmology, 2025)
Corneal dystrophies are a group of predominantly rare inherited disorders. They are by definition bilateral, relatively symmetrical, and without systemic involvement, affecting corneal transparency and/or refraction. Traditional classification of corneal dystrophies is based on slit-lamp appearance, affected corneal layer and histological features. Molecular genetics has provided ultimate proof for the existence of distinct corneal dystrophies and discarded duplicates in their terminology. Currently, there are at least 16 genes with identified pathogenic variants implicated in corneal dystrophies. Herein, we summarise contemporary knowledge on genotype-phenotype correlations of corneal dystrophies, including a critical review of some reported variants, along with the understanding of the underlying pathogenic dystrophic process; essential knowledge for the development of targeted therapies.
Keywords: Corneal Dystrophies, Hereditary; hereditary; molecular biology; genotyp; genetické asociační studie; fenotyp; Mutation; mutace; Phenotype; lidé; corneal dystrophy; dědičné dystrofie rohovky; genetics; Humans; Molecular Biology; molekulární biologie; Genotype; Genetic Association Studies